1993
DOI: 10.1148/radiology.187.2.8475293
|View full text |Cite
|
Sign up to set email alerts
|

Abnormalities of articular cartilage in the knee: analysis of available MR techniques.

Abstract: In an attempt to improve the detection of chondral abnormalities with magnetic resonance imaging, a fat-suppressed three-dimensional gradient-recalled acquisition in the steady state (GRASS) and spoiled GRASS (SPGR) sequence was optimized by study of five cadaveric knee specimens. Results with this optimized sequence then were compared with results with three spin-echo (T1-, proton-density-, and T2-weighted) and two three-dimensional gradient-recalled echo sequences (GRASS and non-fat-suppressed SPGR) in the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
165
3
8

Year Published

1999
1999
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 334 publications
(182 citation statements)
references
References 0 publications
6
165
3
8
Order By: Relevance
“…Because MRI detects subchondral changes, more superficial lesions are less likely to be imaged [25]. Other MRI factors that may affect accuracy include the type of sequence [5,16,17,27], power of the magnet [11,12,26], and positioning [21]. The articular cartilage in the ankle is thinner than in the knee [23], there is close tibiotalar apposition, and the bony anatomy is more complex, all of which could complicate accurate observation of chondral lesions by MRI in the ankle as compared with the knee.…”
Section: Discussionmentioning
confidence: 99%
“…Because MRI detects subchondral changes, more superficial lesions are less likely to be imaged [25]. Other MRI factors that may affect accuracy include the type of sequence [5,16,17,27], power of the magnet [11,12,26], and positioning [21]. The articular cartilage in the ankle is thinner than in the knee [23], there is close tibiotalar apposition, and the bony anatomy is more complex, all of which could complicate accurate observation of chondral lesions by MRI in the ankle as compared with the knee.…”
Section: Discussionmentioning
confidence: 99%
“…MR sequences used for semiquantitative scoring of cartilage lesions involve T 1 -weighted spoiled gradient recalled acquisition at steady state (SPGR ¼ spoiled gradient echo or FLASH ¼ fast low-angle shot) with fat suppression (38,(40)(41)(42)(43)(44)(45)(46)(47) the internal structure of the cartilage displays a more heterogeneous signal and 'internal' pathological changes may be more readily displayed. Also, cartilage surface lesions are well depicted with these sequences, because of the steep gradient of signal intensity between the cartilage and the synovial fluid, in particular when effusion is present [ Fig.…”
Section: Semiquantitative Scoring Of Articular Tissues In Oa Hardwarementioning
confidence: 99%
“…Satisfactory specificity and sensitivity for detecting chondral lesions has been demonstrated in cadaveric knees and in vivo with arthroscopic verification (40)(41)(42)(48)(49)(50)53). Bredella et al (51) reported a sensitivity of 93% and a specificity of 99% in detecting chondral lesions versus athroscopy when axial and coronal images were combined, and values of 94/99% when images in all three planes were combined.…”
Section: Technical Accuracy and Precision Of Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of magnetic resonance imaging (MRI) has made it possible to delineate articular cartilage in vivo (Recht et al, 1993;Peterfy et al, 1994;Eckstein et al, 1996). In conjunction with state-of-the-art three-dimensional (3D) postprocessing tools (qMRI) the technique has been shown to produce accurate and precise data on the cartilage morphology (volume, thickness, and surface area) of the knee in healthy individuals (Stammberger et al, 1999a;Hohe et al, 2002), and in patients with femorotibial osteoarthritis (OA) (Burgkart et al, 2001).…”
mentioning
confidence: 99%